The Effect of Internship Experience on Student Work Readiness at UM - Muhammad Khwarizmi (Universitas Muhammadiyah Malang, 2022)
This study seeks to develop and examine research on the concept of internship experience and its relationship to student work readiness. This study aims to examine the concept of internship experience on job readiness for students at Universitas Negeri Malang. The research population was 275 students consisting of all management students at Universitas Negeri Malang Management class 2018. The number of samples used was 63 students as respondents using the accidental sampling for the sampling technique. The data is processed using SmartPLS 3.0. The results showed that the internship experience had an effect on the work readiness of students at the State University of Malang. That is, the longer the internship experience, the more mature the work readiness possessed by students.